Parathyroid adenoma: a comprehensive biochemical and histological correlative study. (20th October 2016) - Stern, S.; Mizrachi, A.; Strenov, Y.; Knaanie, A.; Benbassat, C.; Shpitzer, T.; Bachar, G.
Abstract : Objective: To investigate the controversial relationship between preoperative calcium and parathyroid hormone levels and the dimensions and histological features of parathyroid adenoma in patients with primary hyperparathyroidism. Study design: Historical cohort. Setting: Tertiary medical centre. Subjects and methods: Clinical and tumour‐related data were collected from the medical files of all patients who underwent parathyroidectomy for primary hyperparathyroidism in 1996–2012. Preoperative blood parathyroid hormone and calcium levels and urine calcium levels were correlated with the size, weight and volume of the parathyroid adenoma. Pathohistological features were determined in a representative sample of archived paraffin‐embedded sections and analysed by calcium or parathyroid hormone level (high/low) and adenoma weight (high/low). Results: A total of 378 patients were included. There was a statistically significant direct correlation of preoperative calcium and parathyroid hormone levels with tumour dimensions and of tumour weight and chief‐cell percentage. At a preoperative calcium level >11.5 mg/dL and parathyroid hormone (PTH) level >165 mg/dL, we predict that the adenoma would measure more than 2.7 g, 2.18 cm and volume of 3.59 cm 3 . Conclusions: In patients with primary hyperparathyroidism, preoperative calcium and PTH levels may be predictive of parathyroid adenoma dimensions.